Regulation of the Actin Cytoskeleton by Thrombin in Human Endothelial Cells: Role of Rho Proteins in Endothelial Barrier Function - Vouret-Craviari, Valérie (The American Society for Cell Biology, 1998)
Endothelial barrier function is regulated at the cellular level by cytoskeletal-dependent anchoring and retracting forces. In the present study we have examined the signal transduction pathways underlying agonist-stimulated reorganization of the actin cytoskeleton in human umbilical vein endothelial cells. Receptor activation by thrombin, or the thrombin receptor (proteinase-activated receptor 1) agonist peptide, leads to an early increase in stress fiber formation followed by cortical actin accumulation and cell rounding. Selective inhibition of thrombin-stimulated signaling systems, including Gi/o (pertussis toxin sensitive), p42/p44, and p38 MAP kinase cascades, Src family kinases, PI-3 kinase, or S6 kinase pathways had no effect on the thrombin response. In contrast, staurosporine and KT5926, an inhibitor of myosin light chain kinase, effectively blocked thrombin-induced cell rounding and retraction. The contribution of Rho to these effects was analyzed by using bacterial toxins that either activate or inhibit the GTPase. Escherichia coli cytotoxic necrotizing factor 1, an activator of Rho, induced the appearance of dense actin cables across cells without perturbing monolayer integrity. Accordingly, lysophosphatidic acid, an activator of Rho-dependent stress fiber formation in fibroblasts, led to reorganization of polymerized actin into stress fibers but failed to induce cell rounding. Inhibition of Rho with Clostridium botulinum exoenzyme C3 fused to the B fragment of diphtheria toxin caused loss of stress fibers with only partial attenuation of thrombin-induced cell rounding. The implication of Rac and Cdc42 was analyzed in transient transfection experiments using either constitutively active (V12) or dominant-interfering (N17) mutants. Expression of RacV12 mimicked the effect of thrombin on cell rounding, and RacN17 blocked the response to thrombin, whereas Cdc42 mutants were without effect. These observations suggest that Rho is involved in the maintenance of endothelial barrier function and Rac participates in cytoskeletal remodeling by thrombin in human umbilical vein endothelial cells.